Partnership on paper, pragmatism on the ground: the European Union's engagement with civil society organisations. Issue 6 (17th August 2020) - Keijzer, Niels; Bossuyt, Fabienne
ABSTRACT: This article analyses the evolution of the European Union's development policy in relation to civil society. Based on a review of overall policy trends, strategies and practices in Central Asia, it demonstrates how the EU's development policy has gradually moved from a focus on European NGOs towards civil society organisations, broadly defined and increasingly associated with the private sector and local authorities. While the EU's policy recognises the intrinsic value of civil society in all its diversity and promotes partnership, its operational practices show a pragmatic preference for working with professionalised organisations in service delivery roles.